The Role of Customer-Focused Strategies in Achieving Sustainable Competitive Advantage in The Indonesian Outsourcing Industry - Soekotjo, Sundari; Lestari, Setyani Dwi; Muhdaliha, Eryco; Saputro, Adi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to understand the Role of Customer-Focused Strategies in Achieving Sustainable Competitive Advantage in the Indonesian Outsourcing Industry. This study adopts a qualitative research approach, conducting in-depth interviews with senior executives and managers from leading outsourcing companies in Indonesia. The interviews are focused on understanding the customer-focused practices of the companies, the challenges they face, and the perceived impact on their competitive position. The collected data is then analyzed using thematic analysis to identify key themes and insights. This research also reviews relevant academic literature and industry reports to contextualize the findings and identify best practices from other countries and sectors. The analysis results indicate that the key elements of a successful customer-focused strategy are a deep understanding of customer needs, the ability to tailor service offerings, effective employee engagement and empowerment, and the development of a company-wide culture that prioritizes customer focus and innovation.